2007
DOI: 10.1186/1471-2334-7-75
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of infection with Toxoplasma gondii in healthy blood donors of Durango, Mexico

Abstract: Background: Toxoplasma gondii (T. gondii) infection in blood donors could represent a risk for transmission in blood recipients. There is scarce information about the epidemiology of T. gondii infection in blood donors in Mexico. Therefore, we sought to determine the prevalence of T. gondii infection and associated sociodemographic and behavioral characteristics in a population of healthy blood donors of Durango City, Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
51
5
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 21 publications
18
51
5
4
Order By: Relevance
“…High seroprevalence of T. gondii with age detected in this study is consistent with other studies conducted on this subject [11,[17][18]. The increase in risk of acquiring Toxoplasma for elder people may be due to a longer lifetime exposure of these people to Toxoplasma-contaminated environmental sources.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High seroprevalence of T. gondii with age detected in this study is consistent with other studies conducted on this subject [11,[17][18]. The increase in risk of acquiring Toxoplasma for elder people may be due to a longer lifetime exposure of these people to Toxoplasma-contaminated environmental sources.…”
Section: Discussionsupporting
confidence: 92%
“…In some areas, such as northeast Brazil, north India and Egypt, more than 50% of blood donors have been seropositive for Toxoplasma infection [11,14,16]. Lower rate of infection in blood donors have been reported from Taiwan (9.3%), Thailand (9.6%), Mexico (7.4%) or Turkey (19.5%) [10,15,[17][18].…”
Section: Introductionmentioning
confidence: 99%
“…These variations in the seroprevalence of anti-T. gondii antibodies among childbearing age women in different parts of Iran might be related to geographical and environmental factors, and transmission routes in the studied population, sampling method, types of laboratory tests and tools, cut off point for positive test (positive test definition), etc. (Alvarado-Esquivel et al 2007;Haghdoost et al 2007). The obtained results exhibited that both contact with cats and consumption of raw/half-cocked meat are significant risk factors for T. gondii seropositivity, which indicated that, among childbearing age women in this study, both infection routes, the ingestion of oocysts (animal to human transmission) and that of tissue cysts in meat (food-borne transmission), existed, similar to the infection routes reported in other studies (Khazaei et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, it was found that contact with cats, consumption of raw vegetables, raw-milk/egg consumption, and drinking clean water (as potential risk factors for acquiring toxoplasmosis) were associated with the seropositivity of T. gondii (2,44). However, no difference was found between education, raw-milk/egg consumption, and blood transfusion on the one hand seroprevalence of anti-T. gondii antibodies on the other.…”
Section: Discussionmentioning
confidence: 67%